Archives of the Communist Czechoslovak State Security on A. V. Issatschenko - Dittmann, Robert (Bohemica Olomucensia, 2018)
Alexander Vasiľevich Issatschenko (1911-1978), one of the prominent and most inspiring Slavists of the 20th century, was a long-term object of interest of the Czechoslovak Communist State Security.The contribution attempts to present the archival materials collected and fragmentarily preserved especially in the Archive of the Security Services in Prague, Czech Republic.
Keywords: A. V. Issatschenko; Czechoslovakia; State Security